2016
DOI: 10.1021/acs.analchem.6b02063
|View full text |Cite
|
Sign up to set email alerts
|

Simple LC-MS Method for Differentiation of Isobaric Phosphatidylserines and Phosphatidylcholines with Deuterated Mobile Phase Additives

Abstract: Lipids from different classes sometimes can exhibit the same exact mass upon electrospray ionization; this presents an analytical challenge in lipidomics. In the negative ionization mode, for example, this can occur with phosphatidylcholines (PCs) and phosphatidylserines (PSs), making them indistinguishable in the absence of fragmentation data. PSs are found at low concentrations in biological samples, making MS/MS spectra difficult to obtain. Moreover, while PCs and PSs are distinguishable in the positive mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Structurally informative peaks pertaining to the fatty acyl chains attached to the glycerol backbone are known to be obtained from CID of the negatively charged glycerophospholipids. 13,14,15,19,20,22,23,24 Conventionally, solution additives, such as ammonium acetate can be used to generate adduct anions in the negative mode. A single acetate adduction at the quaternary ammonium site neutralizes the 13 C-TrEnDi-modified species and there are no other sites for the adduction of a second acetate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Structurally informative peaks pertaining to the fatty acyl chains attached to the glycerol backbone are known to be obtained from CID of the negatively charged glycerophospholipids. 13,14,15,19,20,22,23,24 Conventionally, solution additives, such as ammonium acetate can be used to generate adduct anions in the negative mode. A single acetate adduction at the quaternary ammonium site neutralizes the 13 C-TrEnDi-modified species and there are no other sites for the adduction of a second acetate.…”
Section: Resultsmentioning
confidence: 99%
“…5,12,13,14 However, these gas-phase adducts often have low stability and can inadvertently form isobaric species when applied to complex mixtures. 15,16,17,18 An alternative approach has been to derivatize PLs prior to ionization both to improve the ionization responses of PE and PS lipids in the positive mode 2,19 and to facilitate the distinction of isobaric species 10,12,16 . One such derivatization technique is trimethylation enhancement using 13 C-diazomethane ( 13 C-TrEnDi) modification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved identification of lipids is an important direction for future development in biochemistry because of their roles in metabolism and signaling. Identification of lipids is difficult; grouping mass spectral features into (sometimes broad) lipid classes is the Supplemental Material can be found at: current state of the art (15,16). For this proof-of-principle study, we monitored the turnover of four previously identified lipids, but the techniques can be applied to any identifiable molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in lipid types or concentrations allow boundaries between tissues, as well as regions within the tissue, to be identified (7)(8)(9)(10)12). The spectra from modern highresolution mass spectrometers are exceptionally information rich; but even so, positive identification of all ions in a spectrum is rarely possible and it is often difficult to unambiguously assign peaks to individual lipids (15,16). As a result, many studies have been published using changes in unidentified features to differentiate between areas of an image (8,9).…”
mentioning
confidence: 99%